Crazy love : a memoir - Morgan, Leslie, 1965- (New York : St. Martin's Press, 2009)
Takes you inside the violent, devastating world of abusive love. Conor said love and rage danced intimately together in his psyche. Why didn't Leslie leave? Had she fallen into love-- or into a psychological trap?
Includes bibliographical references and index.
Keywords: Morgan, Leslie, -- 1965-; Abused wives -- United States -- Biography; Abused women -- United States -- Case studies; Family violence -- United States; Femmes victimes de violence -- Biographies; Femmes victimes de violence; Violence familiale; Morgan, Leslie, -- 1965-; Abused wives; Abused women; Family violence; United States; BIOGRAPHY; Autobiographies; Biographies; Case studies; Autobiographies; Case studies; Autobiographies